PERWUJUDAN PERLINDUNGAN HAK DIFABEL IMPLEMENTASI PERWALI NO. 28 TAHUN 2022 DI DINAS SOSIAL KOTA MOJOKERTO - Angel, Avrilia; Muhaimin, Hikmah; Ayu Amelia, Nadia; Rizka Tianle, Nabella (Universitas Islam Majapahit, Indonesia, 2024)
This research effort aims to examine the implementation of Mojokerto Mayor Regulation Number 28 of 2022 and to determine the impact of the implementation of the Mojokerto City Social Service P3A in implementing Mojokerto City Mayor Regulation Number 28 of 2022. This study uses a qualitative descriptive methodology, combining interview techniques, documentation, data validity assessment, extended observation, continuous observational involvement, and triangulation. Primary data were obtained through interviews with informants from the Mojokerto City Social Service P3A and recipients of disability assistance, while secondary data were obtained from literature studies related to the implementation of Mojokerto City Mayor Regulation No. 28 of 2022. The results of the study indicate that the implementation of the mayor's regulation No. 28 of 2022 concerning Disability Protection by the Mojokerto City Social Service P3A has shown effectiveness and success in achieving policy objectives. The integration of this policy with programs such as